Español (Castilla. Estudios de Literatura, 2024)
Review.Technologies of the Self. Woman, Subject and Subjectivity compiles the research carried out by the members of the Research Group "Thought, Creation and Representation in the field of Cultural Studies (PeCRaEC)" under the direction of Dr. Ángeles Mateo del Pino, who edits this volume.